Modulating Inflammation in PCOS: The Role of a High-Protein, Low-Carb Diet in Reducing IL-6 and TNF-α - Hany Puspita Aryani; Lilis Suryani; Sugiyanta (Public Health of Indonesia, 2026)
Background: Polycystic ovary syndrome (PCOS) is a chronic endocrine disorder characterized by insulin resistance and low-grade inflammation, marked by elevated cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Nutritional modulation may play a role in managing these inflammatory markers. Objective: This study aimed to assess the effect of a low-carbohydrate high-protein (RKTP) diet on IL-6 and TNF-α levels in a PCOS-insulin resistance rat model. Methods: This experimental study used a post-test only control group design involving 18 female Rattus norvegicus rats. The rats were divided into three groups: negative control (K−), positive control (K+; PCOS-insulin resistance induced by testosterone propionate), and treatment (P; PCOS-insulin resistance treated with RKTP diet composed of 40% carbohydrates, 30% protein, and 30% fat). The intervention lasted 48 days. Serum levels of IL-6 and TNF-α were measured using ELISA. Data were analyzed using ANOVA, Kruskal-Wallis, and Mann-Whitney tests. Results: The treatment group experienced a significant reduction in IL-6 levels compared to the positive control (p = 0.038) and negative control (p = 0.002). TNF-α levels also significantly decreased in the treatment group (mean = 4.17) compared to the negative control group (mean = 8.83), with a Mann-Whitney test p-value of 0.025. These findings suggest an anti-inflammatory effect of the RKTP diet in PCOS-induced insulin resistance. Conclusion: A high-protein, low-carbohydrate diet effectively reduced inflammatory cytokines in PCOS-insulin resistant rats, suggesting potential as a non-pharmacologic intervention in PCOS management. Keywords: RKTP diet; PCOS-RI; IL-6 Levels; TNF-α Levels